On network-aware clustering of Web clients. - Krishnamurthy, Balachander
Being able to identify the groups of clients that are responsible for a significant portion of a Web site's requests can be helpful to both the Web site and the clients. In a Web application, it is beneficial to move content closer to groups of clients that are responsible for large subsets of requests to an origin server. We introduce clusters---a grouping of clients that are close together topologically and likely to be under common administrative control. We identify clusters using a ``network-aware" method, based on information available from BGP routing table snapshots.
Keywords: Computer systems organization; Computer communication networks; Local and wide area networks; Internet (e.g., TCP/IP).; Design; Experimentation; Measurement; Performance; Reliability; Theory